2021
DOI: 10.1038/s41598-021-90600-0
|View full text |Cite
|
Sign up to set email alerts
|

Immune spleen cells attenuate the inflammatory profile of the mesenteric perivascular adipose tissue in obese mice

Abstract: The perivascular adipose tissue (PVAT) differs from other fat depots and exerts a paracrine action on the vasculature. The spleen has an important role in the immune response, and it was observed to have either a protective role or a contribution to obesity-related diseases. However, the relation between spleen and PVAT is elusive in obesity. We investigated the role of spleen in the inflammatory profile of the mesenteric PVAT (mPVAT) from mice fed a high-fat diet (HFD) for 16 weeks. Male C57Bl/6 mice were sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Therefore, HFHFD-induced metabolic dysfunction with chronic inflammation might be a conceivable reason for thrombocytosis. Interestingly, long-term high-fat diet treatment caused leukopenia and TNF-α increase in mice [ 44 ]. In the present study, HFHFD significantly induced leukopenia, mainly due to the decrease in lymphocytes ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HFHFD-induced metabolic dysfunction with chronic inflammation might be a conceivable reason for thrombocytosis. Interestingly, long-term high-fat diet treatment caused leukopenia and TNF-α increase in mice [ 44 ]. In the present study, HFHFD significantly induced leukopenia, mainly due to the decrease in lymphocytes ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The proximity of PVAT to blood vessels underscores its role in tonal regulation via its secretory modulators [106][107][108]. The capacity to secrete such diverse arrays of biologically active molecules is due to the heterogeneous composition of PVAT which includes not only adipocytes, but leucocytes, neurons, and multipotent progenitor cells [108][109][110]. There are many types of immune cells in PVAT, such as CD4 + and CD8 + T cells, B cells, natural killer (NK) cells, macrophages, mast cells, and neutrophils [106,108,110].…”
Section: Origins Morphology and Immune Cell Composition Of Perivascul...mentioning
confidence: 99%
“…A randomized, double-blind intervention trial involving middle-aged and elderly subjects with overweight or mild hypertension showed that a hot water extract of C. longa containing bisacurone decreased the serum levels of C-reactive protein, IL-6, TNF-α, and VCAM-1 [14]. The expression of inflammatory markers is increased in secondary lymphoid organs, in addition to liver and adipose tissues, in diet-induced obese mice [15,16]. However, the effects of bisacurone on the pro-inflammatory responses of immune cells in the lymphoid tissues remain unclear.…”
Section: Bisacurone Reduces Serum Levels Of Lipids and Blood Viscosit...mentioning
confidence: 99%
“…The expression of inflammatory markers is increased in secondary lymphoid organs, in addition to liver and adipose tissues, in diet-induced obese mice [15,16]. However, the effects of bisacurone on the pro-inflammatory responses of immune cells in the lymphoid tissues remain unclear.…”
Section: Introductionmentioning
confidence: 99%